(untitled) (Bangladesh Journal of Public Administration, 2022)
60-hour long training is a continuous professional development programme for the public servants of the people’s republic of Bangladesh. This training aims at the capacity development of the public servants, which in turns contributes to the organisational performance. 60-hour long training in a year for the employees of public sector in different public sector organisations across the country has been undertaken to raise the skills and competencies and modify the attitude of the public servants under the supervision of MOPA. Since its introduction in 2016, the efficacy of 60-hour long Training programme has not been explored yet. Therefore, this study aims at filling in this gap in literature in public sector, focusing on the trainings offered to employees and its influence on their performance in these organisations. How the outcome of the 60-hour training leads to increased organisational performance is yet to be ascertained. Interpretive approach has been adopted in this study. Data have been collected from selected upazilas of two districts (Moulvibazar, Habiganj) and three Ministries, namely, Ministry of Public Administration, Ministry of Education and Ministry of Health. The findings of the study show that training characteristics consist of before-the-training, during-the-training and after-the-training characteristics. The characteristics of these three stages of training that influence training effectiveness of the 60-hour training in this study comprise: learning readiness of the trainees, pre-training facilitation and activities, environment of training, training method, performance of trainer and style, training contents, training objectives and results. Research findings suggest the strongest important relationships between the characteristics of training such as pre-training, during-the-training and post-training that in turn contribute to the effectiveness of the 60-hour training. Sixty-hour trainin, Efficacy, before-the-training, during-the-training and after-the-training characteristic